Saponin content of lucerne fodder and its effect on rumen fermertation ad microbial population in crossbred bulls - MALIK, P K; SINGHAL, K K (The Indian Journal of Animal Sciences, 2011)
Among the 3 different cuts of lucerne fodder, highest saponin content (2.0% on DM basis) was recorded in second cut. Effect of lucerne fodder (second cut) or its saponin content i.e. 60 mg/kg DM was detennined on DMI, rumen fennentation and microbial population in crossbred bulls. Six male crossbred (Holstein Friesian x Sahiwal) bulls were randomly divided into 2 groups of 3 each on the basis of their body weights. Group 1 was fed on TMR-I consisting of wheat straw and concentrates mixture (60:40) while group 2 was fed on TMR-2 consisting of wheat straw, lucerne fodder (second cut) and concentrate (30:'30:40). DM intake, NH3-N (mg/100mI) and TVFA (m molll) concentration was not affected significantly by the dietary supplementation of lucerne fodder at 30% level (saponin content 60 mg/kg DM). However, saponin supplementation decreased (PÂ